2018
DOI: 10.1186/s12906-018-2367-6
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine and adenosine-5′-monophosphate ingestion ameliorates abnormal glucose metabolism in mice fed a high-fat diet

Abstract: BackgroundWe have previously reported that ingestion of adenosine (ADN) and adenosine-5′-monophosphate (AMP) improves abnormal glucose metabolism in the stroke-prone spontaneously hypertensive rat model of non-obesity-associated insulin resistance. In this study, we investigated the effect of ADN and AMP ingestion on glucose metabolism in mice with high-fat diet-induced obesity.MethodsSeven-week-old C57BL/6 J mice were administered distilled water (as a control), 10 mg/L ADN, or 13 mg/L AMP via their drinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This may be due to higher levels of circulating fatty acids and systemic inflammation, including fat and intestinal inflammation, in OP mice than in OR mice. As a result, OP mice exhibit higher serine phosphorylation of insulin receptor substrate 1 (IRS-1) and more severe insulin signaling blocking (Johnson and Olefsky, 2013 ; Ardiansyah et al, 2018 ). In addition, different metabolites produced by the gut microbiota of OP and OR mice, such as SCFAs and bile acids, enter the circulation and pass through G-protein coupled receptors (GPCRs), nuclear hormone receptors or host proteins post-translational modifications (such as lysine acetylation), thereby affecting whole-body insulin sensitivity (Johnson and Olefsky, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to higher levels of circulating fatty acids and systemic inflammation, including fat and intestinal inflammation, in OP mice than in OR mice. As a result, OP mice exhibit higher serine phosphorylation of insulin receptor substrate 1 (IRS-1) and more severe insulin signaling blocking (Johnson and Olefsky, 2013 ; Ardiansyah et al, 2018 ). In addition, different metabolites produced by the gut microbiota of OP and OR mice, such as SCFAs and bile acids, enter the circulation and pass through G-protein coupled receptors (GPCRs), nuclear hormone receptors or host proteins post-translational modifications (such as lysine acetylation), thereby affecting whole-body insulin sensitivity (Johnson and Olefsky, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, dietary AMP supplementation was shown to increase the food intake by promoting the expression of AgRP and shortening the feeding interval, which is consistent with a previous study in aquatic ( 18 ), which reported that dietary 0.1% AMP supplementation contributed to the food intake of red sea bream ( 18 ). This can be attributed to the reason that the adenosine in food AMP can be absorbed into the body and reduce the concentration of glucose after meal ( 33 , 34 ). Studies have also shown that high levels of glucose after a meal reduce the AMP/ATP ratio in rats ( 35 ), or also reduce the level of AgRP in isolated hypothalamic cultures ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…AMP is known as a purine nucleotide and participant in ATP metabolism. Studies have proved that AMP can be absorbed into the circulatory system and participate in metabolism ( 33 , 37 ). Here, we also found that AMP can be absorbed into the blood from the serum kinetic curve, which is consistent with the previous studies ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine is an important regulator of cellular metabolism that is produced from adenosine triphosphate (ATP) in the intracellular space [15] . Studies have suggested adenosine to mediate anti-inflammatory, anti-oxidative and energy homeostatic effects via enhancement of glucose uptake and inhibition of lipolysis [16] , [17] , [18] . Adenosine receptors, expressed on various cells including hepatocytes modulate metabolic and inflammatory processes such as glutathione synthesis, glucose production and liver control of renal Na+/water balance [19] .…”
Section: Introductionmentioning
confidence: 99%